ChemInform Abstract: Heavier Alkaline Earth Catalyzed Ene‐yne Cyclizations: Atom‐Efficient Access to Tetrahydroisoquinoline Frameworks. Issue 18 (May 2015) - Reid, Stephanie; Barrett, Anthony G. M.; Hill, Michael S.; Procopiou, Panayiotis A.
Abstract Intermolecular alkene hydroamination may be coupled with intramolecular alkyne hydroamination, catalyzed by inexpensive and abundant alkaline earth precatalysts to provide entry to a variety of tetrahydroisoquinoline frameworks.